The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017 XXXIInd General Assembly and Scientific Symposium of the International Union of Radio Science (URSI GASS) 2017
DOI: 10.23919/ursigass.2017.8105136
|View full text |Cite
|
Sign up to set email alerts
|

Visible light communication based on offset pulse position modulation (Offset-PPM) using high power LED

Abstract: In this paper, the performance of a visible light communication (VLC) system based on offset pulse position modulation (Offset-PPM) has been demonstrated using a commercial high power white single LED (30 W) and the new coding scheme. Data at a speed of 11 Mbps has been successfully transmitted over a distance of 1 m with zero bit error rate (BER), and 18 Mbps with 1.15 × 10 of BER through the simplest transceiver circuits.Keywords-bit error rate; offset pulse position modulation; visible light communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…By moving one digit from the least significant towards the most significant, the next code words in the sequence will be produced [6]. Ahfayd et al [7] studied the spectrum properties of OPPM, MPPM, and truncated PPM. This in turn has concluded that the OPPM can produce distinct lines compared to DPPM.…”
Section: Offset Pulse Position Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…By moving one digit from the least significant towards the most significant, the next code words in the sequence will be produced [6]. Ahfayd et al [7] studied the spectrum properties of OPPM, MPPM, and truncated PPM. This in turn has concluded that the OPPM can produce distinct lines compared to DPPM.…”
Section: Offset Pulse Position Modulationmentioning
confidence: 99%
“…RS is represented in this study to recover the error causes that plague the OPPM. PE is specifically used to critically represent the symbol-error likelihood encoded by RS as illustrated in (7).…”
Section: Error Correction Code 31 Reed-solomon Error Correctionmentioning
confidence: 99%
“…Regardless of the fact that the RS technique can increase packet error rate performance during error detection, Reed and Solomon (1960) established DiPPM's dominance in analyzing defects properly. Additionally, the MLSD error corrector can be used to reduce DiPPM mistakes accumulated during transmission as recommended by Al‐Nedawe [10]. The Reed Salmoon solves the DiPPM error sources by considerably reducing the number of mistakes that happened during transmission.…”
Section: Introductionmentioning
confidence: 99%
“…At the frame repetition frequency, OPPM creates distinct lines, but digital PPM does not, thus OPPM seems to have a strong frame element. Three bits of PCM are converted into four-bit codewords using the OPPM method [8].…”
Section: Introductionmentioning
confidence: 99%
“…For the improvement and mitigation of transmission quality and the effects of inter symbol interference (ISI) respectively an investigation was conducted with dicode pulse position modulation technique (DiPPM) [15]. In previous experiments by the others, offset pulse position modulation technique has been implemented using a 30 W LED based VLC equipment achieving a data rate of 11 Mbps [16].…”
Section: Introductionmentioning
confidence: 99%